2018
DOI: 10.1515/intag-2016-0091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of monovalent cations on soil structure. Part I. Results of an Iranian soil

Abstract: A b s t r a c t. This study investigated the impact of monovalent cations on clay dispersion, aggregate stability, soil pore size distribution, and saturated hydraulic conductivity on agricultural soil in Iran. The soil was incubated with treatment solutions containing different concentrations (0-54.4 mmol l -1 ) of potassium and sodium cations. The treatment solutions included two levels of electrical conductivity (EC=3 or 6 dS m -1 ) and six K:Na ratios per electrical conductivity level. At both electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
3
15
1
1
Order By: Relevance
“…The results with regard to the impact of K on soil structure presented in this paper are apparently in contradiction to the findings presented in Part I of this series of papers (Farahani et al, 2018). Here, we demonstrate that clay dispersion was little affected by K and tended to decrease with increasing K concentration (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The results with regard to the impact of K on soil structure presented in this paper are apparently in contradiction to the findings presented in Part I of this series of papers (Farahani et al, 2018). Here, we demonstrate that clay dispersion was little affected by K and tended to decrease with increasing K concentration (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…1), while we found that K strongly increased clay dispersion in Part I of our work ( Fig. 1 in Farahani et al, 2018). The si l soil used in this paper had a similar texture as the soil used in Part I, and the experimental procedure (the addition of monovalent cations in treatment solutions and incubation for one month) and treatment concentrations (K in the range of 0-60 mmolc l -1 ) were similar in both studies.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…There was no correlation between net dispersive charge and Na concentration (sum of water‐soluble and exchangeable Na). Furthermore, the percentage of dispersible clay increased significantly with increasing K concentration ( r = 0.92, P = 0.004 and r = 0.77, P = 0.04 for EC 3 and 6 dS m −1 , respectively) and K:Na ratios ( r = 0.74, P = 0.05 and r = 0.78, P = 0.03 for EC 3 and 6 dS m −1 , respectively), but no relation was obtained between clay dispersion and Na concentration (Farahani et al ., ). Similar results, for a negative effect of K on soil structure, especially clay dispersion, have been reported in soils with different textures (sandy loam, loamy sand, loam, clay loam and clay) and clay mineralogy (mixture of kaolinite and illite, illite, kaolinite and smectite) in the literature (Czyz et al ., ; Rengasamy & Marchuk, ; Marchuk & Rengasamy, ; Emami et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Cropping system management plays an important role in the construction and modification of the geomorphology and soil structure of sloping agricultural landscapes (De Alba et al, 2004;Arnáez et al, 2015). Inadequate conservation practices can promote a continuous degradation of soil structure (Nunes et al, 2017), resulting in the dispersion of particles as a result of the presence of unstable aggregates, impeding the retention of rainwater and favouring the displacement of these particles, thereby facilitating erosion (Beutler et al, 2001;Farahani et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%